Analisis Unsur-unsur Komunikasi, Media Komunikai, Metode Komunikasi, Efek Komunikasi - Efendi, Erwan; Andy Akbar; Arizah Laila Madani; Luthfyah Az Zahra; Mhd. Sabili Al Ghozi Nst; Utsman Fajri Ramadhan. (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Analysis of Communication Elements, Communication Media, Communication Methods, Communication Effects Communication methods are the concrete way messages are conveyed, such as direct speaking, letters, telephone, email, or presentations. The seven elements of communication play a very important role in building a successful and good communication process. Communication media includes all types of content used in the communication process, including text. Communication methods include the techniques and methods used to send messages from the sender to the recipient. This includes oral communication, tert. Communication effects refer to the impact of messages conveyed through certain media or communication methods. Analysis of communication elements, media selection, use of appropriate methods and strategies, and understanding the effects of communication are very important in ensuring that messages are conveyed effectively and achieve the desired goals in various contexts, both in personal communication and public communication.